2020
DOI: 10.3390/ijms21124515
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy-Related 2 Regulates Chlorophyll Degradation under Abiotic Stress Conditions in Arabidopsis

Abstract: Chloroplasts are extraordinary organelles for photosynthesis and nutrient storage in plants. During leaf senescence or under stress conditions, damaged chloroplasts are degraded and provide nutrients for developing organs. Autophagy is a high-throughput degradation pathway for intracellular material turnover in eukaryotes. Along with chloroplast degradation, chlorophyll, an important component of the photosynthetic machine, is also degraded. However, the chlorophyll degradation pathways under high light intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 66 publications
2
14
0
Order By: Relevance
“…Arabidopsis has a single ATG2 gene that is expressed ubiquitously throughout the plant. The atg2 knockout mutants display typical autophagy-defective phenotypes during senescence and stress conditions [ 73 , 74 ]. The T-DNA insertion Arabidopsis mutant atg2-5 shows impaired low-CO 2 -induced stomatal opening.…”
Section: The Role Of Core Autophagy Components In Plant Abiotic Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Arabidopsis has a single ATG2 gene that is expressed ubiquitously throughout the plant. The atg2 knockout mutants display typical autophagy-defective phenotypes during senescence and stress conditions [ 73 , 74 ]. The T-DNA insertion Arabidopsis mutant atg2-5 shows impaired low-CO 2 -induced stomatal opening.…”
Section: The Role Of Core Autophagy Components In Plant Abiotic Stressmentioning
confidence: 99%
“…The fresh weight and chlorophyll retention of atg2-1 mutants are dramatically decreased compared with those of wild-type (WT) plants under high-temperature conditions. The mRNA levels of ATG5, ATG6, ATG12A and ATG18A also significantly increase in WT plants under high-temperature conditions [ 74 ]. In addition, autophagy plays a role in resetting the cellular memory of heat stress (HS).…”
Section: The Role Of Core Autophagy Components In Plant Abiotic Stressmentioning
confidence: 99%
“…In fact, the atg5-1 , atg7-2, and nbr1-1 mutants are all hypersensitive to heat stress (37 °C or 45 °C) [ 53 , 59 ]. In comparison, the atg2-1 mutant shows a only slight phenotype at 30 °C with a lower fresh weight and chlorophyll amount compared to WT [ 60 ]. Nevertheless, the atg2-1 mutant and the atg5-1 , atg7-2, and atg10-1 mutants all show an alteration in pollen development and anthers dehiscence after treatment at 30 °C [ 61 ].…”
Section: Autophagy a Series Of Intense Membrane Remodeling Events Controlling Plant Responses To Environmental Stressesmentioning
confidence: 99%
“…Recently it was shown that the atg2 , atg5 , atg7 , atg10 , atg12a, and atg18a mutants were hypersensitive to a treatment with UV-B leading to a half reduction in the activity of PSII in comparison with the WT [ 66 , 67 ]. A high visible light treatment also induced a necrosis phenotype in the atg2-1 mutant [ 60 ]. In addition, several autophagy mutants, including atg7-1 [ 42 ], atg5-1 [ 44 ], and atg13a/atg13b [ 29 ], exhibit accelerated senescence of their rosette leaves when cultivated in short days suggesting the importance of autophagy in the management of cell homeostasis and plant development upon different photoperiods.…”
Section: Autophagy a Series Of Intense Membrane Remodeling Events Controlling Plant Responses To Environmental Stressesmentioning
confidence: 99%
See 1 more Smart Citation